Pendidikan Cloud-Based Accounting pada Mahasiswa Akuntansi di Perguruan Tinggi di Surabaya: Dampak Human, Economic and Technological, Cultural and Social Factors - Zukhrotun Naima Ahmad; Vicky Vendy (Jurnal Riset Pendidikan Ekonomi, 2026)
This study aims to determine the influence of human, economic and technological, cultural and social factors on the development of cloud-based accounting education. The sample in this study consists of 119 accounting students at higher education institutions in Surabaya. The data in this study uses primary data obtained directly through the distribution of questionnaires to respondents. This type of research is explanatory research with a quantitative approach. The data was analyzed using SEM-PLS. The results of the study indicate that human factors and economic and technological factors have a significant positive influence on the development of cloud-based accounting education. On the other hand, cultural and social factors do not have a significant influence on the development of cloud-based accounting education. This study can contribute by showing that human factors, economic and technological factors can influence the development of cloud-based accounting education. Conversely, cultural and social factors need to be considered by educators regarding attitudes, traditions, dand cultural trends that are temporary and easily changeable, which unrealistically encourage the acceptance of new technology, thus potentially hindering trust in cloud-based accounting users.